Productivity and performance of irrigated wheat farms across canal commands in the Lower Indus Basin - Hussain, I.; Marikar, F.; Jehangir, Waqar A. (International Water Management Institute, 2000)
A study of the enormous differences in agricultural productivity that exist across farms and regions in Pakistan, where, for example, recent farm-level data from Sindh, indicates that irrigated wheat output per hectare varies from 0.5 to 5.4 tons across farms. Looks at the central goal of agricultural policy in the country, viz. improving and sustaining productivity, narrowing the existing productivity gaps, and enhancing resource use efficiencies to meet food requirements of a rapidly growing population.